2012
DOI: 10.1002/poc.2950
|View full text |Cite
|
Sign up to set email alerts
|

Remote substituent effects on homolytic Fe‐N bond energies of p‐G‐C6H4NHFe(CO)25‐C5H5) and p‐G‐C6H4(COMe)NFe(CO)25‐C5H5) studied using Hartree–Fock and density functional theory methods

Abstract: The nature and strength of metal-ligand bonds in organotransition-metal complexes is crucial to the understanding of organometallic reactions and catalysis. The Fe-N homolytic bond dissociation energies [ΔH homo (Fe-N)′s] of two series of para-substituted Fp anilines p-G-C 6 H 4 NHFp [1] and p-G-C 6 H 4 N(COMe)Fp [2] were studied using the Hartree-Fock (HF) and the density functional theory methods with large basis sets. In this study, Fp is (h 5 -C 5 H 5 )Fe(CO) 2 and G are NO 2 , CN, COMe, CO 2 Me, CF 3 , Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Indeed, metal–ligand bond enthalpies can provide valuable information on metal–ligand bonding, can offer a deeper insight into known reaction pathways, and can aid in designing new transformations . Unfortunately, the experimental determination of metal–ligand bond dissociation energy (BDE) in organometallic complexes is often difficult . Density functional theory (DFT), however, has proven to be a powerful alternative in this effort, especially after the development of nonlocal and hybrid DFT methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, metal–ligand bond enthalpies can provide valuable information on metal–ligand bonding, can offer a deeper insight into known reaction pathways, and can aid in designing new transformations . Unfortunately, the experimental determination of metal–ligand bond dissociation energy (BDE) in organometallic complexes is often difficult . Density functional theory (DFT), however, has proven to be a powerful alternative in this effort, especially after the development of nonlocal and hybrid DFT methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are scarce reports on the Fe–O and Fe–S bond energies in Fp compounds . In our laboratory, methods described by Venimadhavan et al ., Bordwell et al ., and Brauman for determining enthalpies of heterolysis (Δ H het ) and homolysis (Δ H homo ) for the cleavage of N–H, C–H, O–H, or C–S bonds were extended to the study of Fe–O and Fe–S σ‐bond energies through the reactions of para‐substituted phenoxide ions ( p ‐G‐C 6 H 4 O − ) or para‐substituted thiophenyl anions ( p ‐G‐C 6 H 4 S − ) with Fp + BF 4 − formed in solution.…”
Section: Introductionmentioning
confidence: 99%
“…It can be found that Δ H homo (Fe–N)'s from columns IV to V in series 1 are smaller than the corresponding Δ H homo (Fe–N)'s in series 2 , respectively. This results from the electron withdrawing effect of α‐COMe . They also have the comparable magnitudes with those in Fe(porphyrin)(NO) and Fe(porphyrin)(imidazole)(NO) whose Δ H homo (Fe–NO)'s are 35 and 36 kcal/mol calculated by DFT methods …”
Section: Resultsmentioning
confidence: 62%
“…In b , the Fe 1 –N 9 and N 9 –C 13 bond lengths and the ∠Fe 1 –N 9 –C 13 and ∠N 9 –Fe 1 –C 2 (88.0°) bond angles are different from the corresponding data in a notably. It results from the inductive effect and steric effect of α‐COMe on N 9 atom …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation